Amplified backscattering in RFID communications with energy harvesting tags - Ünalan, Denizhan. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in the Social Sciences, 2018., 2018)
The main objective of this thesis is to investigate the backscatter modulation based radio-frequency identiﬁcation (RFID) communication with energy harvesting tags. Thus, the study analyzes the impacts of energy harvesting on ampliﬁed backscat tering and evaluates the average read probability of the RFID tags over fading channel scenarios. Two diﬀerent RFID system models are constructed: the delay-constrained, which is similar to the conventional passive RFID system, and delay-tolerant, which presents a new type of an RFID system. Then a heuristic transmit power policy opti mization algorithm is proposed for the backscatter modulated signals in both models in order to maximize the average read probability. By maximizing the average read probability, the optimal values of the average read probability are calculated. The optimal and simulation results are in tight agreement with each other. Thus, the tags with energy harvesting capability improve the average read probability performance of RFID communication. Furthermore, the study proves that when a chance of delay is given to the energy harvesting tag, the read probability increases signiﬁcantly.
Keywords: Radio frequency identification systems.; Energy harvesting.